Over-the-top business models for the sports broadcasting industry: from a direct-to-consumer streaming platform to a direct-to-consumer ecosystem - a business model optimization - Riou, Aurélie (2021)
The operation of a Direct-to-Consumer over-the-top platform of rights owners is related to high financial risks, as the revenues of media rights sales are lost. The analysis investigated how the profitability and competitiveness of rights owners Direct-to-Consumer streaming platforms can be improved through the development of a Direct-to-Consumer Ecosystem. The suggested business model optimization consists of integrating betting, daily fantasy sports and sports-related merchandising on the streaming platform to increase average revenue per user and fan engagement. The technological implementation of these services is assured by the supplier surplus, while operational capabilities have to be developed in-house.